Kondisi Aspek Biologi Reproduksi Ikan Silais (Kryptopterus hexapterus) di Sungai Bilah Kabupaten Labuhanbatu - Khairul, Khairul; Sari, Rina (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Aspects of reproductive biology are important information in efforts to monitoring fish resources. Aspects of reproductive biology of K. hexapterus to be observed include: sex ratio, Gonadal Maturity Rate, and Gonadal Maturity Index. Fish sampling was carried out in October â€“ December 2021 using splint net fishing gear. Determination of observation stations by purposive sampling method, where based on the location of fishermen install splint nets. The results obtained the sex ratio of male and female K. hexapterus (1: 0.34).Â  Male of the Gonadal maturity Rate only at levels I-II while females are level I-IV. It can be concluded based on the results of the study, that there is too much difference in the ratio between male and female fish caught, so that Gonadal maturity Rate of male fish is not obtained that is ready to spawn. However, in female fish there are already those who reach Gonadal maturity Rate IV phase, this means they are ready to spawn. Male of the Gonad Maturity Index (0.12 - 0.43%) and female (0.11 - 2.98%). Conditions like these can make it difficult for female fish to find males who are also gonadally mature and equally ready to spawn.